2011
DOI: 10.5194/hess-15-75-2011
|View full text |Cite
|
Sign up to set email alerts
|

A dynamic approach for evaluating coarse scale satellite soil moisture products

Abstract: Abstract.Validating coarse scale remote sensing soil moisture products requires a comparison of gridded data to pointlike ground measurements. The necessary aggregation of in situ measurements to the footprint scale of a satellite sensor (>100 km 2 ) introduces uncertainties in the validation of the satellite soil moisture product. Observed differences between the satellite product and in situ data are therefore partly attributable to these aggregation uncertainties. The present paper investigates different ap… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(40 citation statements)
references
References 54 publications
3
37
0
Order By: Relevance
“…In this study, the UM has a horizontal resolution of about 40 km and therefore an error of representativity of 0.06 m 3 m −3 in the USDA SCAN observations is assumed. This error of representativity value is consistent with Miralles et al (2010) who consider smaller spatial scales ranging from 12 km to 25 km and Loew and Schlenz (2011). Since USDA SCAN is a sparse network, it is not possible to use spatial averaging to reduce the error of representativity in the USDA SCAN Forecast Range (hours) observations.…”
Section: Comparison Of Model With In-situ Soil Moisture Measurementssupporting
confidence: 71%
“…In this study, the UM has a horizontal resolution of about 40 km and therefore an error of representativity of 0.06 m 3 m −3 in the USDA SCAN observations is assumed. This error of representativity value is consistent with Miralles et al (2010) who consider smaller spatial scales ranging from 12 km to 25 km and Loew and Schlenz (2011). Since USDA SCAN is a sparse network, it is not possible to use spatial averaging to reduce the error of representativity in the USDA SCAN Forecast Range (hours) observations.…”
Section: Comparison Of Model With In-situ Soil Moisture Measurementssupporting
confidence: 71%
“…8, is that daytime observations from both satellites become of higher quality when the vegetation density increases compared to the night-time observations over the same areas. Several studies (Loew and Schlenz, 2011;Brocca et al, 2011) indicated this already, but none of them explained this phenomenon. One possible explanation is that the vegetation water content during the day decreases due to transpiration induced by photosynthesis, making the vegetation more transparent to microwave emission, and consequently increasing the sensitivity to the underlying soil moisture signal.…”
Section: Ka-band Scenariosmentioning
confidence: 99%
“…These effects can give rise to temporal autocorrelation in errors and undermine the linearity assumption between coincident measures. Finally, the non-stationary characteristic of noise in satellite SM (Loew and Schlenz , 2011;Zwieback et al, 2013;Su et al, 2014a) due to e.g. dynamical land surface characteristics such as soil moisture (Su et al, 2014b), is not treated here.…”
Section: Multi-scale Decomposition Of Soil Moisturementioning
confidence: 99%
“…One possible remedy is to apply bias correction, either TC or statistical-moment matching, only to anomaly time series (Miralles et al, 2011;Liu et al, 2012;Su et al, 2014a), but it remains unclear how these methods affect the signal and noise components in the corrected data. Alternatively a moving time window can be used to examine the time-varying statistics of time series (Loew and Schlenz , 2011;Zwieback et al, 2013;Su et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%